Current and emerging tools for simultaneous assessment of infection and rejection risk in transplantation - Tharmaraj, Dhakshayini; Mulley, William R.; Dendle, Claire (Frontiers in Immunology, 2024)
Infection and rejection are major complications that impact transplant longevity and recipient survival. Balancing their risks is a significant challenge for clinicians. Current strategies aimed at interrogating the degree of immune deficiency or activation and their attendant risks of infection and rejection are imprecise. These include immune (cell counts, function and subsets, immunoglobulin levels) and non-immune (drug levels, viral loads) markers. The shared risk factors between infection and rejection and the bidirectional and intricate relationship between both entities further complicate transplant recipient care and decisionmaking. Understanding the dynamic changes in the underlying net state of immunity and the overall risk of both complications in parallel is key to optimizing outcomes. The allograft biopsy is the current gold standard for the diagnosis of rejection but is associated with inherent risks that warrant careful consideration. Several biomarkers, in particular, donor derived cell-free-DNA and urinary chemokines (CXCL9 and CXCL10), show significant promise in improving subclinical and clinical rejection risk prediction, which may reduce the need for allograft biopsies in some situations. Integrating conventional and emerging risk assessment tools can help stratify the individual's short-and longer-term infection and rejection risks in parallel. Individuals identified as having a low risk of rejection may tolerate immunosuppression (IS) wean to reduce medication-related toxicity. Serial monitoring following IS reduction or escalation with minimally invasive tools can help mitigate infection and rejection risks and allow for timely diagnosis and treatment of these complications, ultimately improving allograft and patient outcomes.